The maqasid filter in takaful audit - Yussof, Sheila Ainon; Soualhi, Younes (The Malaysian Current Law Journal Sdn Bhd, 2012)
Introduction : Islamic financial institutions in conducting regular audits must look for evidences in their contracts, processes and activities that genuinely support the goals and objectives of the Shari'ah (maqasid al-Shari'ah). The maqasid of the Shari'ah concerning all kinds of economic wealth can be summarised under five parameters/criteria: 'adl (justice) in handling it; wuduh (transparency); hifz (preservation); thabat (durability); and rawaj (marketability) or a fair circulation of wealth in the hands of as many people as possible. Specific issues identified in family takaful operations are used to determine whether the application of the maqasid filter based on the above criteria can help assure halal and wholesome profits that are enhanced by the maslahah or public benefit of growth and preservation and just distribution of wealth and the attainment of sustainability goals to support future generations.